Precarious employment and health of outsourced workers in a public educational institution (Research, Society and Development, 2022)
Outsourcing is part of the job insecurity process and can be defined as a procedure in which an activity is carried out for an organization, however, the hiring of professionals occurs through an intermediary company. The research aimed to analyze the work and the health of outsourced workers (n = 18) who worked in the warehouse sector of a public educational institution. The theoretical and methodological framework of the investigation came from the Clinic of Activity. A case study was carried out using data from an intervention. Constructive-interpretative analysis was used on the contents of the records produced during the intervention. The results indicated differences in remuneration and benefits. Inadequate working conditions were also found: environment with poor structure; exposure to dangerous products and inappropriate equipment. It was also observed the authoritarianism and centralizing attitudes of a manager, which reduced workers' autonomy and subjected them to vexing situations. It was concluded that these professionals are subject to accidents, diseases, harassments, threats, disrespect and prejudice due to precarious work conditions.